UMPSA staff and students inspired by screening of ‘Mereka Yang Tertewas’ - Jamilah Bebe, Mohamad (UMPSA, 2024)
KUANTAN, 13 November 2024 – A group of staff and students from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) had the privilege of attending a special screening of the film Mereka Yang Tertewas.